Lecture notes on the concept and practice of FSR to improve cattle milk and meat production in sub-Saharan Africa - Asamenew, G. (International Livestock Centre for Africa, 1991)
This paper discusses particularly the approach that may need to be followed in cattle milk and meat research in a farming systems perspective. The key characteristics of on-farm research, an integral part of farming systems research, are summarised, and the stages of farming systems research related to cattle milk and meat research in a farming systems perspective are discussed with ref. to target area selection, description and diagnosis, as well as design, testing and evaluation.